Decreasing frequency and improved outcomes of hepatitis C‐related liver transplantation in the era of direct‐acting antivirals – a retrospective cohort study. (26th March 2019) - Arora, Sumant S.; Axley, Page; Ahmed, Zunirah; Satapathy, Sanjaya K.; Wong, Robert; Kuo, Young‐Fang; Singal, Ashwani K.
Summary: Benefit of direct‐acting antivirals (DAA) for hepatitis C virus (HCV) on clinical outcomes is unclear. We examined temporal trends in liver transplant (LT) listings, receipt of LT, re‐LT, and survival between pre‐DAA (2009–2012) and DAA era (2013–2016) using UNOS database. Of 32 319 first adult LT, 15 049 (47%) were performed for HCV. Trends on listing, first LT, and of re‐LT for HCV showed 23%, 20%, and 21% decrease in DAA compared to pre‐DAA era ( P  < 0.0001). One‐year liver graft and patient survival among HCV LT improved in DAA era (90% vs. 86% and 92% vs. 88%, respectively, P  < 0.0001). Non‐HCV LT showed no improvement in survival (89% vs. 89% and 92% vs. 92.4%, P  = NS). On cox regression, compared to non‐HCV LTs in DAA era, LT for HCV in pre‐DAA era had worse patient survival (HR 1.56 [1.04–2.35]). The outcome was similar when compared to LTs for HCV in DAA era and for non‐HCV in pre‐DAA era. Burden of HCV‐related LT waitlist and LT is declining in DAA era, with improved post‐transplant outcomes, more so in later than earlier DAA era. Our findings negate recent Cochrane meta‐analysis on DAA therapy and encourage studies to examine HCV clinical outcomes outside LT setting.